2016
DOI: 10.3389/fevo.2016.00010
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Oxidative stress as a cost of reproduction: beyond the simplistic trade-off model

David Costantini

Abstract: A commentary onOxidative stress as a cost of reproduction: beyond the simplistic trade-off model by Speakman, J. R., and Garratt, M. (2014). Bioessays 36, 93-106. doi: 10.1002/bies.201300108 Current theory proposes that life history traits cannot be simultaneously maximized because there are costs paid in the currency of fitness when a change in one trait, for example increased reproduction, results in a detrimental change in another, for example decreased survival. The underlying reasoning is that resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…The negative effects of damage from ROS have been proposed to include future ability to compete, attract mates, allocate resources to reproduction, and support processes that combat senescence (Sohal and Weindruch, 1996;von Schantz et al, 1999;Costantini, 2008;Monaghan et al, 2009;Metcalfe and Monaghan, 2013). Yet empirical evidence does not consistently show that an increase in ROS production is harmful (Speakman and Selman, 2011;Costantini, 2014Costantini, , 2016Speakman and Garratt, 2014;Blount et al, 2015;Mowry et al, 2016). In the present study, we showed no differences in ROS emission or oxidative damage in the tissues studied other than higher 4-HNE levels in liver of the females that ran and reproduced.…”
Section: Discussioncontrasting
confidence: 69%
“…The negative effects of damage from ROS have been proposed to include future ability to compete, attract mates, allocate resources to reproduction, and support processes that combat senescence (Sohal and Weindruch, 1996;von Schantz et al, 1999;Costantini, 2008;Monaghan et al, 2009;Metcalfe and Monaghan, 2013). Yet empirical evidence does not consistently show that an increase in ROS production is harmful (Speakman and Selman, 2011;Costantini, 2014Costantini, , 2016Speakman and Garratt, 2014;Blount et al, 2015;Mowry et al, 2016). In the present study, we showed no differences in ROS emission or oxidative damage in the tissues studied other than higher 4-HNE levels in liver of the females that ran and reproduced.…”
Section: Discussioncontrasting
confidence: 69%
“…As a result, it is not possible to identify which physiological mechanism may best mediate a cost of reproduction in this species. Nevertheless, our study compared investment in offspring care by breeders and alloparents across their natural range of variation, which has been suggested to represent a powerful comparison to explore the physiological underpinnings of the cost of reproduction (Costantini, 2016a;Speakman and Garratt, 2014). Regardless of whether manipulating investment in offspring care would have unveiled a cost of reproduction in superb starlings, our study suggests that in free-living cooperative breeders where individuals can select their contribution to parental or alloparental care, individuals did not incur a short-term cost of offspring care as measured across diverse physiological systems.…”
Section: Discussionmentioning
confidence: 99%
“…It is under these types of harsh environments (compared with a laboratory environment where food is provided ad libitum) that the cost of reproduction is most likely to be elevated and detectable (Erikstad et al, 1998;Speakman and Garratt, 2014). Second, cooperatively breeding species are ideal systems to explore how natural variation in care shapes the cost of rearing offspring (Costantini, 2016a;Speakman and Garratt, 2014) because care involves a combination of parental and alloparental forms. In superb starlings, investment in offspring care is highly variable from one individual to the next (Guindre-Parker and Rubenstein, 2018b), making it possible to explore whether individuals that invest most in caring for offspring pay a greater cost of reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between reproduction and oxidative stress has been proposed by several researchers (Metcalfe & Monaghan, ), but further research is needed to define and understand the differences among species and reproductive strategies. Reproduction is an energetically expensive process for females, increasing resource requirements, metabolism (Angilletta & Sears, ) and potentially the production of ROS (Costantini, ,b; Metcalfe & Alonso‐Alvarez, ; Metcalfe & Monaghan, ). Oxidative costs of reproduction have been demonstrated in females of numerous species, including wild Song Sparrows ( Melospiza melodia ) (Travers, Clinchy, Zanette, Boonstra, & Williams, ), the viviparous Asp Viper ( Vipera aspis ) (Stier et al., ), Brown Boobies ( Sula leucogaster ) (Montoya, Valverde, Rojas, & Torres, ), Zebra Finches ( Taeniopygia guttata ) (Noguera, ) and White‐Browed Sparrow‐Weavers ( Plocepasse mahali ) (Cram, Blount, & Young, ).…”
Section: Introductionmentioning
confidence: 99%